Implementation of the Lexical Approach to Increase Learning Activeness in Arabic Vocabulary Mastery for Class III Students at SD IT Al-Hikmah Pekanbaru - Jannah, Raudatul; Karim, Promadi (Prodi Pendidikan Bahasa Arab, Universitas Muhammadiyah Tangerang, 2024)
This research is an experimental research with data collection using observation and student debriefing sheets, the participants were 16 students with three meetings in class III at Al-Hikmah integrated Islamic elementary school. This research aims to determine the extent to which students are active in learning to master Arabic vocabulary using a lexical approach. So the results obtained were that the lexical approach was able to increase students' activeness in learning Arabic vocabulary mastery. The highest activity presentation with a percentage of 100% was table number 1, 2 and 14, then the second best activity with a percentage of 83% was table number 3, 4, 5. , 8, 11, 12, and 13. And the lowest activity with a percentage of 50% is table number 9. It is also known that there was a significant increase in the first meeting with a score of 60% then increased in the second meeting to 85% then in the third meeting it increased to 96 %. This shows that the lexical approach is effective in increasing the learning activity of Al-Hikmah Pekanbaru integrated Islamic elementary school students. Keywords: Lexical Approach, vocabulary mastery, student activity and improvement.